Exosomal and Non‐Exosomal Urinary miRNAs in Prostate Cancer Detection and Prognosis - Foj, Laura; Ferrer, Ferran; Serra, Marta; Arévalo, Antonio; Gavagnach, Montserrat; Giménez, Nuria; Filella, Xavier (The Prostate, 2017)
BACKGROUND MicroRNAs (miRNAs) are non‐coding small RNAs, involved in post‐transcriptional regulation of many target genes. METHODS Five miRNAs that have been consistently found deregulated in PCa (miR‐21, miR‐141, miR‐214, miR‐375, and let‐7c) were analyzed in urinary pellets from 60 prostate cancer (PCa) patients and 10 healthy subjects by qRT‐PCR. Besides, urinary exosomes were isolated by differential centrifugation and analyzed for those miRNAs. RESULTS Significant upregulation of miR‐21, miR‐141, and miR‐375 was found comparing PCa patients with healthy subjects in urinary pellets, while miR‐214 was found significantly downregulated. Regarding urinary exosomes, miR‐21 and miR‐375 were also significantly upregulated in PCa but no differences were found for miR‐141. Significant differences were found for let‐7c in PCa in urinary exosomes while no differences were observed in urinary pellets. A panel combining miR‐21 and miR‐375 is suggested as the best combination to distinguish PCa patients and healthy subjects, with an AUC of 0.872. Furthermore, the association of miRNAs with clinicopathological characteristics was investigated. MiR‐141 resulted significantly correlated with Gleason score in urinary pellets and let‐7c with clinical stage in urinary exosomes. Additionally, miR‐21, miR‐141, and miR‐214 were found significantly deregulated in intermediate/high‐risk PCa versus low‐risk/healthy subjects in urinary pellets. Significant differences between both groups were found in urinary exosomes for miR‐21, miR‐375, and let‐7c. CONCLUSIONS These findings suggest that the analysis of miRNAs—especially miRNA‐21 and miR‐375‐ in urine could be useful as biomarkers in PCa. Prostate 77: 573–583, 2017. © 2016 Wiley Periodicals, Inc.